2018
DOI: 10.1007/s10811-018-1427-0
|View full text |Cite
|
Sign up to set email alerts
|

Effect of microalgae hydrolysate foliar application (Arthrospira platensis and Scenedesmus sp.) on Petunia x hybrida growth

Abstract: In horticultural practice, accelerated plant development, and particularly earlier flowering, has been reported with microalgae applications. Therefore, the objective of this work was to study the effects of foliar spraying with Scenedesmus sp. and Arthrospira platensis hydrolysates on Petunia x hybrida plant development and leaf nutrient status. Three treatments were tested: T1 (foliar application with water, the control), T2 (foliar application with Arthrospira) and T3 (foliar application with Scenedesmus). … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
82
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 107 publications
(102 citation statements)
references
References 25 publications
2
82
0
Order By: Relevance
“…These results could demonstrate the presence of molecules with biological activity such as gibberellins, which are a group of plant hormones that play an important role in the initiation of seed germination and stem elongation [32,33]. As it is shown in Table 1, the higher germination indexes of watercress seeds were obtained for treatments without hydrolyzing the biomass, that is T1 and T2 (undisrupted biomass) and T5 and T6 (disrupted biomass).…”
Section: Gibberellin-like Effect Germination Indexmentioning
confidence: 74%
See 1 more Smart Citation
“…These results could demonstrate the presence of molecules with biological activity such as gibberellins, which are a group of plant hormones that play an important role in the initiation of seed germination and stem elongation [32,33]. As it is shown in Table 1, the higher germination indexes of watercress seeds were obtained for treatments without hydrolyzing the biomass, that is T1 and T2 (undisrupted biomass) and T5 and T6 (disrupted biomass).…”
Section: Gibberellin-like Effect Germination Indexmentioning
confidence: 74%
“…This fact could explain the inhibitory effect at higher concentrations (2 g/L). Plaza et al (2018) [33] analyzed the hormone content of the hydrolyzed of Scenedesmus sp. and Arthrospira sp.…”
Section: Responsementioning
confidence: 99%
“…Microalgae have a huge benefit as resource to supply the increasing demand of protein and amino acids for food and feed [1], biofertilizers and biostimulants [2], bulk chemicals [3], and bioactives [4]. Nevertheless, economic constraints have hampered the development of these applications, which in general have limited microalgae uses to high-value bioproducts [5][6][7].…”
Section: Introductionmentioning
confidence: 99%
“…The microalga may have potentially prevented the loss of nutrients as the result of N, P and K being released slowly, as an organic fertilizer, based on the plant's needs. Plaza et al (2018) found that a foliar application of scenedesmus hydrolysates was also seen to have increased the leaf and shoot number and improve foliar Ca, Mg, K and P levels.…”
Section: Photosynthetic Pigmentsmentioning
confidence: 92%
“…Microalga are the world's largest oxygen-producing organisms and are crucial for planetary functions and sustainability of the ecosystem. Following the application of microalga products, plants have been reported to have exhibited different responses, such as robust growth, increased yield, improved nutrient uptake, increased biotic and abiotic stress resistance (fungal infections, pest attacks and frost), increased quality and fruit with a longer shelf life (Plaza et al, 2018;Singh et al, 2018a;Righini et al, 2018). Algae are comprised of active compounds, like organic and free amino acids, enzymes and phytohormones, as well as bioactive secondary metabolites, vitamins, vitamin precursors (Plaza et al, 2018), essential nutrients and plant growth regulators like auxins and cytokinins (Righini et al, 2018).…”
Section: Introductionmentioning
confidence: 99%